Strategi Psikologi Guru dan Kepala Madrasah dalam Meningkatkan Kualitas Pembelajaran - Linda Yuli Agustin; Khairulanwar Deesaeh; Siti Maryamah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
The quality of learning is one of the important factors in the success of the educational process. Teachers and principals have a very important role in creating effective and quality learning. Therefore, appropriate psychological strategies are needed in managing learning as well as improving teacher motivation and performance. This study aims to determine the psychological strategies used by teachers and principals in improving the quality of learning. The research method used in this study is a literature review by analyzing several journals related to educational management and educational psychology. The results of the study show that psychological strategies such as teacher work motivation, principal leadership, effective communication, and organizational conflict management can improve the quality of learning in educational institutions. In addition, the application of psychological approaches can create a more positive school climate, strengthen cooperation among educational stakeholders, and support the development of professional teacher behavior. The findings indicate that the success of learning quality improvement depends not only on instructional techniques, but also on emotional, motivational, and leadership factors within the school environment.